Dengue NS1 interaction with lipids alters its pathogenic effects on monocyte derived macrophages - Dayarathna, S; Senadheera, B; Jeewandara, C; Dissanayake, M; Bary, F; Ogg, GS; Malavige, GN (BioMed Central, 2024)
Background: While dengue NS1 antigen has been shown to be associated with disease pathogenesis in some studies, it has not been linked in other studies, with the reasons remaining unclear. NS1 antigen levels in acute dengue are often associated with increased disease severity, but there has been a wide variation in results based on past dengue infection and infecting dengue virus (DENV) serotype. As NS1 engages with many host lipids, we hypothesize that the type of NS1-lipid interactions alters its pathogenicity. Methods: Primary human monocyte derived macrophages (MDMs) were co-cultured with NS1 alone or with HDL, LDL, LPS and/or platelet activating factor (PAF) from individuals with a history of past dengue fever (DF = 8) or dengue haemorrhagic fever (DHF = 8). IL-1β levels were measured in culture supernatants, and gene expression analysis carried out in MDMs. Monocyte subpopulations were assessed by flow cytometry. Hierarchical cluster analysis with Euclidean distance calculations were used to differentiate clusters. Differentially expressed variables were extracted and a classifier model was developed to differentiate between past DF and DHF. Results: Significantly higher levels of IL-1β were seen in culture supernatants when NS1 was co-cultured with LDL (p = 0.01, median = 45.69 pg/ml), but lower levels when NS1 was co-cultured with HDL (p = 0.05, median = 4.617 pg/ml). MDMs of those with past DHF produced higher levels of IL-1β when NS1 was co-cultured with PAF (p = 0.02). MDMs of individuals with past DHF, were significantly more likely to down-regulate RPLP2 gene expression when macrophages were co-cultured with either PAF alone, or NS1 combined with PAF, or NS1 combined with LDL. When NS1 was co-cultured with PAF, HDL or LDL two clusters were detected based on IL10 expression, but these did not differentiate those with past DF or DHF. Conclusions: As RPLP2 is important in DENV replication, regulating cellular stress responses and immune responses and IL-10 is associated with severe disease, it would be important to further explore how differential expression of RPLP2 and IL-10 could lead to disease pathogenesis based on NS1 and lipid interactions.